The Effect of the Application of Warehouse Management System on Goods Storage at PT Shippindo Logistics Technology - Anugrah, Dedek Faisal; Patil, Mithun B (Yayasan Sinergi Kawula Muda, 2023)
This research was conducted at PT Shippindo Teknologi Logistik. The purpose of this study is to determine the results of data analysis from the effect of implementing a warehouse management system on the storage of goods at PT Shippindo Teknologi Logistik. In this study, researchers distributed 100 questionnaires to respondents, and these respondents were directly related to the object of study. The research methodology used in this study is a quantitative research method, using a deductive-inductive approach. The results of data calculation and analysis in this study were processed using the SPSS program. From the calculation results using SPSS, the regression equation results are obtained which are Y = 11.038 + 0.938X0.710. So it can be concluded that it can be found that attitude partially affects consumer buying interest significantly and positively. This can be seen from the results of the t-test stating that the p-value is smaller than the significance value (0.000 < 0.05). In addition, in the attitude variable the calculated value of 4.332> the ttable value of 2.048, the Warehouse Management System variable was declared to have a positive effect. Against the variable storage of goods, it can be concluded that a hypothesis is formed to analyze the influence of the variable.